1998
DOI: 10.1002/(sici)1097-0231(19981030)12:20<1520::aid-rcm336>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-cationized oligosaccharides do not appear to undergo ‘internal residue loss’ rearrangement processes on tandem mass spectrometry

Abstract: The phenomenon of 'internal residue loss' of protonated native- and per-O-methylated oligosaccharides has recently been described as occurring on high-energy collision conditions. Awareness of this phenomenon in the mass spectrometric analysis of oligosaccharides is of great importance since the rearrangement ions produced by this process may complicate monosaccharide sequence assignment. In this research, oligosaccharides having N-acetyl-glucosamine residues as the reducing or non-reducing terminal residue ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 0 publications
1
56
0
Order By: Relevance
“…CID of protonated permethylated species did not give rise to any fucose transfer products. Brüll et al have shown, however, that internal residue loss may occur for both native and permethylated oligosaccharides,15 indicating that capping of the oligosaccharide hydroxyl groups by methyl groups cannot prevent rearrangements in all cases. Due to the limited set of data available, no conclusions can be drawn as to which structural and/or experimental parameters determine the occurrence of fucose transfer in MS/MS of permethylated oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CID of protonated permethylated species did not give rise to any fucose transfer products. Brüll et al have shown, however, that internal residue loss may occur for both native and permethylated oligosaccharides,15 indicating that capping of the oligosaccharide hydroxyl groups by methyl groups cannot prevent rearrangements in all cases. Due to the limited set of data available, no conclusions can be drawn as to which structural and/or experimental parameters determine the occurrence of fucose transfer in MS/MS of permethylated oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…In particular terminal fucose residues show this mobility, but the migration of other residues has also been reported 9–14. In most cases rearrangements were found to occur by monosaccharide transfer to adjacent monosaccharides,9, 11–15 while some cases of long‐distance transfers have also been described, with the destination of the transferred monosaccharide often being the innermost monosaccharide labeled with an aromatic tag 10, 16, 17. This results in the observation of Y‐type ions which have obtained a fucose residue from the leaving group.…”
mentioning
confidence: 91%
“…In these spectra, the diagnostic B‐ions corresponding to Neu5Ac 1 Hex 1 HexNAc 1 ( m/z 657.2) and Neu5Ac 1 Hex 2 ( m/z 638.2) were detected. The absence of an ion at m/z 680.2, corresponding to the sodium adduct of m/z 657.2, confirms that the N‐hexosamine residue preferentially is protonated 17. The ion at m/z 347.1 corresponds to [Hex 2 +Na] + to which sequential addition corresponding to a Hep structure are observed in ions at m/z 539.2 and 830.1 ([Hex 2 Hep 1 +Na] + and [Neu5Ac 1 Hex 3 Hep 1 +Na] + , respectively).…”
Section: Resultsmentioning
confidence: 89%
“…It is well known that the nature of the monosaccharide units that make up an oligosaccharide governs the fragmentation of the compound 17. It has been shown that fragmentation products differ depending on the charge and the coordinating ion (anion or cation) of the species 18.…”
mentioning
confidence: 99%
“…demonstrated that the FAB‐MS/MS internal monosaccharide residue loss was not limited to ions containing 1→2 substituted residues, but also included trisaccharides containing the 1→6‐linked monosaccharide residues . In addition, it was shown that the CID‐MS/MS losses of the internal monosaccharide residue were also observed with sialyl‐Lewis‐type oligosaccharides, anthracycline aminodisaccharides, and other oligosaccharides under low‐energy CID conditions . All these previous studies, involving the elimination of internal monosaccharide residues from oligosaccharides, produced aberrant structures, which were not present originally in the selected precursor molecules.…”
mentioning
confidence: 89%